Evaluation of physiological cost and subjective assessment of existing coconut climibing devices - HAMEEDA BINDU VAHAB; Dr. Bini Sam (Guide) (Tavanur 2015 DEPARTMENT OF FARM POWER MACHINERY AND ENERGY)
Evaluation of physiological cost and subjective assessment of existing coconut climibing devices
Evaluation of physiological cost and subjective assessment of existing coconut climibing devices